Religionskundliches Unterrichtswerk - Kesseler, Kurt; Oppermann, Wilhelm; Schremmer, Bruno; Thomsen, Peter (Verlag von Quelle & Meyer, 1932)
Thematisch geordnete Bibelsprüche, Auszüge aus Luthers kleinem Katechismus, Lieder, Gebete